Reputation, trust, price consciousness, and perceived value of guest booking intention: A study of co-living users - Adriyanti, Sesilia; Hardjono, Retno Kusumastuti (Economic Military and Geographically Business Review, 2025)
Background: The growth of the home-sharing accommodation industry in recent years has increased significantly. Co-living, one of the home-sharing industries, has become an attractive trend in urban real estate because it offers flexibility and shared accommodation. The intention to book co-living accommodation is an important factor in the success of the home-sharing business, especially in co-living services. This study aims to analyze the factors that influence guest booking intention using attribution theory, which consists of reputation, trust, price consciousness, and perceived value variables. Method: This research uses an explanatory type of research with a quantitative approach by distributing online questionnaires to 155 people in JABODETABEK area who have used co-living. Research data analysis using simple linear regression and the Sobel test shows a positive and significant influence between reputation, trust, price consciousness, and perceived value variables on guest booking intention. Findings: The study found that reputation, trust, price consciousness, and perceived value all positively influence guest booking intention. Reputation has a positive influence on booking intention, mediated by trust, while price consciousness affects booking intention through perceived value. Conclusion: Reputation, trust, price consciousness, and perceived value are crucial in shaping guest booking intention in the co-living industry. The mediation of trust and perceived value highlights the complex dynamics influencing booking decisions. Novelty/Originality of this article: This study provides a novel analysis of the factors influencing guest booking intention in the co-living industry, highlighting the mediating roles of trust and perceived value, with a focus on reputation and price consciousness.